The Inflammatory Response of Respiratory System to Metal Nanoparticle Exposure and Its Suppression by Redox Active Agent and Cytokine Therapy - Nikolaev, B.P.; L.Yu.Yakovleva; Mikhalev, V.A.; Marchenko, Ya.Yu.; Gepetskaya, M.V.; Ischenko, A.M.; Slonimskaya, S.I.; Simbirtsev, A.S. (IntechOpen, 2012)
None